National museums : new studies from around the world - Knell, Simon J.; Aronsson, Peter; Bugge Amundsen, Arne; Barnes, Amy Jane; Burch, Stuart; Carter, Jennifer; Gosselin, Viviane; Hughes, Sarah A.; Kirwan, Alan (Milton Park, Abingdon, Oxon : New York : Routledge, 2010)
National museums and the national imagination / Simon J. Knell -- Explaining national museums : exploring comparative approaches to the study of national museums / Peter Aronsson -- Myths of nationality / Donald Preziosi -- Loading guns with patriotic love : Artur Hazelius' attempts at Skansen to remake Swedish society / Mattias Backstrom -- Narrative and imagination : remaking national history at the Musée des monuments français, Paris / Jennifer Carter -- National art museum practice as political cartography in nineteenth-century Britain / Christopher Whitehead -- Placing Britain in the British Museum : encompassing the other / Chris Wingfield -- Producing an art history of the nation : the origins of the Finnish National Gallery / Susanna Pettersson -- Reimagining the nation in museums : Poland's old and new national museums / Karoline Kaluza -- National art museums and the 'modernization' of Turkey / Ayie H. Köksal -- Political change and the national museum in Taiwan / Chi-Jung Chu -- The British Museum in print : from national to universal museum / Sarah A. Hughes -- The nation disrobed : nudity, leisure and class at the Prado / Eugenia Afrinoguenova -- Taking part : performance, participation and national art museums / Stuart Burch -- Representing Wales at the Museum of Welsh Life / Rhiannon Mason.
Same exhibitions, different labels? : Romanian national museums and the fall of communism / Simina Bădică-- Re-thinking Korean cultural identities at the National Museum of Korea / Sunghee Choi -- The aesthetics and narratives of national museums in China / Marizia Varutti -- The Dutch National Historical Museum : a national museum for the twenty-first century / Gwenny Van Hasselt -- Who authors the nation? : the debate surround the building of the new Estonian National Museum / Pille Runnel, Taavi Tatsi, and Pille Pruulmann-Vangerfeldt -- Recounting history : constructing a national narrative in the Hong Kong Museum of History / Emily Stokes-Rees -- Kaesong Koryo Museum : the place of one Korean nation? / Ruth Scheidhauer -- The national museum as palimpsest : postcolonial politics and the National Museum of Korea / Jung Joon Lee -- Exhibiting China in London / Amy Jane Barnes -- Exhibiting the Congo in Stockholm / Otten Gustafsson Reinius -- After the fall of the Berlin Wall : nationalism and multiculturalism at Bulgarian National Ethnographic museum / Radostina Sharenkova -- The Ijzertoren Memorial Museum : a Flemish national museum? / Karen D. Shelby -- Postcolonialism, ethnicity and the National Museum of Ireland / Alan Kirwan -- Facing up to diversity : conversations at the National Museum of Colombia / Cristina Lleras.
boek